Inclusive education - problems and solutions - Saidova Nodira Bahodir qizi (Genius Journals, 2023)
The modern education system fully accepts only those who respond to certain requirements, children with standard capabilities, able to study in a common program for all and show academic results that are normal for all. As a result, it often turns out that children with special educational needs drop out of the general educational process, since the pedagogical staff of general educational institutions does not have the necessary knowledge in the field of correctional and special pedagogy to work with them. In this article will be discussed problems associated with teaching children with special educational needs in the modern school and it’s solutions that can be reached by using inclusive education.
Keywords: Inclusive education; disability; child